Transformation of education policy - Martens, Kerstin; Nagel, Alexander-Kenneth; Windzio, Michael; Weymann, Ansgar (Transformations of the state, 2010)
This book deals with the political consequences of the PISA Study forsecondary education and the Bologna Process for tertiary education. Both are prominent political issues with substantial impact on thepolitical debate all over Europe and beyond. However, scholars of political science and political sociology have been reluctant to give them sufficient attention